Comparative Genomic and Phenotypic Analysis of the Vaginal Probiotic Lactobacillus rhamnosus GR-1 - Petrova, Mariya I.; Macklaim, Jean M.; Wuyts, Sander; Verhoeven, Tine; Vanderleyden, Jos; Gloor, Gregory B.; Lebeer, Sarah; Reid, Gregor (Frontiers in Microbiology, 2018)
Lactobacillus represents a versatile bacterial genus, which can adapt to a wide variety of ecological niches, including human body sites such as the intestinal and urogenital tract. In this study, the complete genome sequence of the vaginal probiotic Lactobacillus rhamnosus GR-1 was determined and compared to other L. rhamnosus strains at genomic and phenotypic level. The strain GR-1 was originally isolated from a female urethra, and was assessed with Lactobacillus rhamnosus GG from a feces sample of a healthy male, and Lactobacillus rhamnosus LC705 from a dairy product. A key difference is the absence in GR-1 and LC705 of the spaCBA locus required for pili-mediated intestinal epithelial adhesion. In addition, the L. rhamnosus GR-1 genome contains a unique cluster for exopolysaccharide production, which is postulated to synthesize glucose-rich, rhamnose-lacking exopolysaccharide molecules that are different from the galactose-rich EPS of L. rhamnosus GG. Compared to L. rhamnosus GG, L. rhamnosus GR-1 was also genetically predicted and experimentally shown to better metabolize lactose and maltose, and to better withstand oxidative stress, which is of relevance in the vagina. This study could thus provide a molecular framework for the selection of the optimal probiotic strain for each targeted niche and condition, but further substantiation of niche adaptation mechanisms of lactobacilli is warranted.